FULL-FACTORY EXPERIMENTAL STUDIES - Dilrabo Mamatova; Abbosjon Nematov; Khosiyat Nurullayeva (Journal Park Publishing, 2022)
The article presents the results of full-factorial experiments to optimize the parameters of the belt drive, as well as the results of production tests of the cleaning machine, the drive of which uses the recommended belt drive. Full-factorial experiments substantiated the values of the frequency of rotation of the peg drum, the eccentricity of the tension roller and the stiffness coefficient of the elastic element, which provides a high cleaning effect.
Keywords: Raw cotton cleaner; fine and coarse litter; peg and saw drums